134P Comprehensive assessment of anti-tumour PDL1 blockade effect in a sarcoma mouse model. (15th December 2019) - Nafia, I; Chaibi, A; Bortolotto, D; Cerf, L; Italiano, A; Bessede, A
Abstract: Background: Development of novel immunotherapeutics in oncology is of crucial interest and their good testing at preclinical stage relies on i) the features of the animal model used and ii) the application of an appropriate comprehensive strategy for the deep delineation of mechanisms underlying resistance/sensitivity to a drug. Methods: Using a syngeneic sarcoma mouse model, treated with anti-PDL1, we investigated by intratumoral microdialysis and flow cytometry the immunometabolic profile and immune landscape of the tumour, respectively. The anti-tumor effect of PDL1 blockade was assessed through tumour growth monitoring and tumoral biopsies were also collected for gene expression analysis. Finally, involvement of CD8 T cells in the anti-tumour PDL1 blockade-mediated activity was addressed using a specific depleting antibody -based strategy. Results: When compared to a non-tumour area, data obtained from tumour microdialysates highlighted i) a slight Kynurenine pathway activation, ii) a strong Arginase activity, and iii) a high Adenosine production. Interestingly, anti-PDL1 effect was associated with a decrease of the tumoral Adenosine level thus arguing for an important role of the Adenosine axis in the control of the anti-tumour immune response. In addition, PDL1 blockade led to an intratumoral CD45+ leukocytes enrichment, with a higher abundance of lymphocytes also displaying increased level of IFNgamma. In contrast, macrophages – CD11b+/F4:80+ - were limited upon treatment, especially the immunosuppressive CD11b/Gr1 Low/Int cellsubsets, in favor of an increase of the M1/M2 macrophages ratio. Interestingly, CD8 depletion fully abrogated anti-PDL1 anti-tumour effect thus showing the unequivocal role of this population. Finally, gene expression analysis revealed, in addition to an interferon signature, changes in genes from the myeloid / neutrophil subsets including Arg1 and key chemokines. Conclusion: Altogether, this multiparametric dataset gives i) a better understanding of intrinsic features of the preclinical model and deeper insights into the mechanism of action of an effective drug, and ii) might serve as a platform combination-based strategy for comprehensive explorations of novel candidates. Legal entity responsible for the study: Alban Bessede. Funding: Explicyte Immuno-Oncology. Disclosure: A. Bessede: Shareholder / Stockholder / Stock options, Full / Part-time employment: Explicyte. All other authors have declared no conflicts of interest.